1. John and Sarah are simplifying this expression.
3a + 8b + 7a – 6b
John says the answer is 2a + 2b and Sarah says the answer is 10a + 14b.
What is the correct answer?
Sarah
2. Simplify these expressions.
a) 4d + 6e – 2d – 3e = 2d-3e b) 12g – 3h – 8g + h = 4g-4h c) k + 2k + 3k – m – 2m – 3m = 6k-3m d) 7c + 4d – 10c + 5d = -3c+9d
3. Multiply out these brackets.
a) 3(2a + 7) = 6a+21 b) 5(3x – 2y) = 15x-10 c) 2(4g2 – 3g) = 8g2-6
4. Expand the brackets and then simplify the expression.
a) 2(x + 8) + 3(x + 1) = 2x+16+3x+3 = 5x+19 b) 3(2x + 3) + 2(2x – 3) = 6x+9+4x-6 = 10x+15 c) 4(2a – 5) + 3(a – 1) = 8a-20+3a-3 = 11a-23 d) 2(4a + 1) – 2(a – 1)= 8a+2-2a-2 = 6a